Efektifitas dan Efisiensi Pengelolaan Keuangan Serta Meminimalisir Moral Hazard Pengelola Keuangan Melalui Implementasi Kartu Kredit Pemerintah - Farida Wijayanti (Otonomi, 2020)
Corporate Credit Card is carried out in order to support cashless society, modernization and applying the principles of accountability and transparaency of state finance management . The purpose of Corporate Credit Card regulation are reducing cash transaction , reducing idle cash and cost of government fund and reducing cash and non cash transaction fraud.. This research was aimed how the implementation of Corporate Credit Card increase effectiveness and efficiency of state finance management and decrease moral hazard behavior at Satuan Kerja KPPN Blitar as object. This Research used qualitative case study approach study with interview result as primary data and observation and document as secondary data. Informers was chosen by purposive sampling. The results of the research conducted, obtained an ability of Corporate Credit Card impelementasion to increase effiectiveness dan efficiency of state finance management and decrease moral hazard behavior Keywords: Corporate Credit Card, Government, Effeiciency, Effectiveness , Moral Hazard.